Instructional Story Design : Develop Stories That Train - Greene, Rance (Association for Talent Development, 2020)
Once Upon a Time, Storytelling Met Instructional Design From children to adults, everybody likes a good story. Stories are memorable, actionable, and emotional. We are constantly making sense of the world by forming stories, and that makes them perfect for instructional design. Instructional Story Design is a practical guide to writing and developing stories for training. It takes what you already know about a story's power to connect with people and offers a clear methodology for the otherwise daunting process of creating a compelling story. Master story designer Rance Greene shares his powerful yet familiar process to discover, design, and deliver instructional stories. He presents the two essential elements that must be present to tell a story for training: relatable characters and strong conflict. These elements create a desire for resolution and grab learners' attention. This book offers advice for unearthing the root of the performance problem, creating action lists for learners, and convincing stakeholders about the effectiveness of stories. Case studies from household companies such as Pizza Hut, Southwest Airlines, and PepsiCo show story design in action. Job aids and resources include an audience profile questionnaire, character description worksheet, storyboard template, and tips for developing stories using graphics, audio, and video. With this book, you'll: Sharpen your analysis skills to discover potential training stories. Design relatable stories that concretely connect with learning objectives. Easily develop captivating stories with tools you already own. Plan your next steps to implement your instructional story.